Certain Sequence Spaces over the Non-Newtonian Complex Field - Sebiha Tekin; Feyzi Başar (Abstract and Applied Analysis)
It is known from functional analysis that in classical calculus, the sets , , , and of all bounded, convergent, null and -absolutely summable sequences are Banach spaces with their natural norms and they are complete according to the metric reduced from their norm, where . In this study, our main goal is to construct the spaces , , , and over the non-Newtonian complex field and to obtain the corresponding results for these spaces, where .